Tribbles expression in cumulus cells is related to oocyte maturation and fatty acid metabolism - Brisard, Daphné (BioMed Central, 2014)
BACKGROUND: In mammals, the Tribbles family includes widely expressed serine-threonine kinase-like proteins (TRIB1, TRIB2 and TRIB3) that are involved in multiple biological processes including cell proliferation and fatty acid (FA) metabolism. Our recent studies highlighted the importance of FA metabolism in cumulus cells (CC) during oocyte maturation in vertebrates and reported a higher TRIB1 expression in CC surrounding in vivo mature oocytes as compared to immature ooocytes in mice and cows. The objective was to investigate Tribbles expression patterns in bovine CC during in vitro maturation (IVM) and to examine their roles in the cumulus-oocyte complex. METHODS: Tribbles gene expression was analyzed in bovine and murine CC using quantitative RT-PCR. Proteins were detected using Western blot and intracellular localization was assessed by immunofluorescence. Bovine COCs were treated with etomoxir, an inhibitor of FA oxidation (FAO) which blocks CPT1 activity, during 6 h and 18 h IVM. Oocyte meiotic stage was assessed and expression of Tribbles and lipid metabolism genes was quantified in CC. RESULTS AND DISCUSSION: TRIB1 and TRIB3 were more strongly expressed whereas TRIB2 was less expressed in CC surrounding the oocytes from preovulatory follicles than in CC of immature ones. In CC, Tribbles were located in the cytoplasm and nucleus; in mitotic cells TRIB2 and TRIB3 were detected in the spindle. In the oocyte, Tribbles proteins were detected in the ooplasm; also TRIB2 and TRIB3 were more accumulated in the germinal vesicle. In bovine CC, expression of TRIB1 and TRIB3 was transiently increased at a time preceding oocyte meiosis resumption in vitro. Treatment with etomoxir (150 μM) during IVM resulted in a significant reduction of oocyte maturation rate and decreased MAPK3/1 phosphorylation in the oocytes. In CC, 18 h IVM of etomoxir treatment significantly increased expression of TRIB1, TRIB3, CPTA1 (enzyme regulating FA entry in mitochondria for FAO) and CD36 (thrombospondin receptor involved in FA transport). Under the same conditions, expression of TRIB2 and ACACA (Acetyl coenzyme A carboxylase involved in FA synthesis) decreased in CC. All considered, Tribbles family members may be involved in cell proliferation and in FAO signaling in CC and participate in oocyte meiotic resumption regulation.